A companion to the archaeology of religion in the ancient world - Raja, Rubina; Rüpke, Jörg (Blackwell companions to the ancient world, 2015)
Part I: Archaeology of ritual -- The archaeology of ancient sanctuaries / William Van Andringa -- Ritual activities, processions and pilgrimages / Thierry Luginbühl -- Perpetuated action / Lara Weiss -- Public and private / Robert Parker -- Part II: Embodiment -- Amulets / Gideon Bohak -- Dress and ornaments / Laura Gawlinski -- Dance / Frederick Naerebout -- Gendered agents and embodied religious experience / Zsuzsanna Várhelyi -- Part III: Experiences -- Polychromy and Jewish visual culture of Roman antiquity /Steven Fine -- Watching rituals / Valérie Huet -- Killing and preparing animals / Patrice Méniel -- Communal dining: making things happen / Marleen Martens -- Water / Olivier de Cazanove -- Temporary deprivation: rules and meanings / Richard Gordon -- Part IV: Creating spaces of experiences -- At home / Kimberly Bowes -- Gardens / Richard Neudecker -- Religion and tomb / Henner von Hesberg, Christiane Nowak and Ellen Thiermann -- Part V: Designing and appropriating sacred space -- Archaeology of Christian initiation / Robin M. Jensen -- Oracular shrines as places of religious experience /Julia Kindt -- Buildings of religious communities / Igne Nielsen -- Sanctuaries and urban spatial settings in Roman imperial Ostia / Marlis Arnhold -- Part VI: Sharing public space -- Complex sanctuaries in the Roman period / Rubina Raja -- Temples and temple interiors / Henner von Hesberg -- Theater /Susanne Gödde -- The archaeology of processions / Eftychia Stavrianopoulou -- Urbanization and memory / Christopher Smith -- Part VII: Expressiveness -- Images /Sylvia Estienne -- Instruments and vessels / Anne Viola Siebert -- Anatomical ex votos / Günther Schörner -- Monumental inscriptions / Wolfgang Spickermann -- Part VIII: Agents -- Material culture and religious identity in late antiquity / Eric Rebillard -- Individual choices and individuality in the archaeology of ancient religion /Jörg Rüpke -- Material culture and imagined communities in the Roman world / Eva Mol and Miguel John Versluys -- Part IX: Transformations -- Ritual traditions of non-Mediterranean Europe / Greg Woolf -- Tracing religious change in Roman Africa / Valentino Gasparini.